The factors influencing the supply of rural elderly services in China based on CHARLS data: Evidence from rural land use and management - Zhao, Yan (Frontiers in Environmental Science, 2022)
The problem of elderly service supply is a realistic issue that must be solved for the in-depth development of an aging society. This paper uses microdata from the China Health and Retirement Longitudinal Study published in 2017 and regression analysis using a dichotomous logistic model. Finally, the article examines the factors that affect the supply of elderly services and land use in rural China. The results show that: i) Health level is the most direct influencing factor on whether rural elderly people in rural land can get the elderly service supply; ii) The family characteristic that affects the elderly service supply in rural land is the relationship of living with children rather than the number of children; iii) The socio-economic status has an impact on the elderly service supply, but the impact is limited; iv) The factors affecting the supply of family elderly services and social elderly services for the rural elderly are basically the same, and the fundamental difference between the two is that the service targets are different, this reflects the characteristics of typology.